2022
DOI: 10.1021/acs.jpclett.2c01505
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Amyloid Fibril Properties Via Ionic Liquids: The Representative Case of Ethylammonium Nitrate and Tetramethylguanidinium Acetate on the Amyloidogenesis of Lysozyme

Abstract: Protein aggregation into amyloid fibrils has been observed in several pathological conditions and exploited in nanotechnology. It is also key in several biochemical processes. In this work, we show that ionic liquids (ILs), a vast class of organic electrolytes, can finely tune amyloid properties, opening a new landscape in basic science and applications. The representative case of ethylammonium nitrate (EAN) and tetramethyl-guanidinium acetate (TMGA) ILs on lysozyme is considered. First, atomic force microscop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Toxicity is, however, also a synonym of affinity, and this have stimulated, in turn, a series of biological and chemical-physical investigations aimed at using the ability of ILs to interact with biosystems to develop applications in bio-nanomedicine and bio-nanotechnology (Egorova et al 2017 ; Benedetto and Ballone 2018 ; Banerjee et al 2018 ; Tanner et al 2020 ; Curreri et al 2021 ; Kumari et al 2021a ; Pillai et al 2022a ; Hu et al 2023 ). For example, it has been shown that the oral delivery of a choline-based IL prevents the absorption of fat molecules through intestinal tissue in rats (Nurunnabi et al 2019 ).…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…Toxicity is, however, also a synonym of affinity, and this have stimulated, in turn, a series of biological and chemical-physical investigations aimed at using the ability of ILs to interact with biosystems to develop applications in bio-nanomedicine and bio-nanotechnology (Egorova et al 2017 ; Benedetto and Ballone 2018 ; Banerjee et al 2018 ; Tanner et al 2020 ; Curreri et al 2021 ; Kumari et al 2021a ; Pillai et al 2022a ; Hu et al 2023 ). For example, it has been shown that the oral delivery of a choline-based IL prevents the absorption of fat molecules through intestinal tissue in rats (Nurunnabi et al 2019 ).…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…The presence of a trace amount of π-stacking-forming toluene solvent in chloroform cannot induce self-assembly . The impact of aqueous ionic liquid (IL) solution on peptide or protein aggregation has received considerable attention. Adding water to HB-forming IL, ethylammonium nitrate (EAN), triggers self-assembling into nanofibrils, different from the no visible structure found in pure ILs . Introduction of water in 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM] + [BF 4 ] − ) induces self-assembly into nanotubes, and no ordered structure is observed in pure IL …”
Section: Introductionmentioning
confidence: 99%
“…Anions such as phosphate and sulfate promoted aggregation, whereas mesylate anion suppressed it due to a competitive anion−water interaction guiding the self-assembly. 17 Very recently, 23 atomic force microscopy have revealed that protic ILs shows a strong influence on the thickness of growth on lysozyme amyloids under different IL concentrations in presence of water. They even conjectured 24 the nanostructuring of protic ILs and the heterogeneous distributions of the ions and water in space using computer simulation study.…”
Section: Introductionmentioning
confidence: 99%